Evolution of chromosome-arm aberrations in breast cancer through genetic network rewiring - Kuzmin, Elena; Baker, Toby M.; Lesluyes, Tom; Monlong, Jean; Abe, Kento T.; Coelho, Paula P.; Schwartz, Michael; Del Corpo, Joseph; Zou, Dongmei; Morin, Genevieve; Pacis, Alain; Yang, Yang; et al. (Cell reports (Cambridge), 2024)
The basal breast cancer subtype is enriched for triple-negative breast cancer (TNBC) and displays consistent large chromosomal deletions. Here, we characterize evolution and maintenance of chromosome 4p (chr4p) loss in basal breast cancer. Analysis of The Cancer Genome Atlas data shows recurrent deletion of chr4p in basal breast cancer. Phylogenetic analysis of a panel of 23 primary tumor/patient-derived xenograft basal breast cancers reveals early evolution of chr4p deletion. Mechanistically we show that chr4p loss is associated with enhanced proliferation. Gene function studies identify an unknown gene, C4orf19, within chr4p, which suppresses proliferation when overexpressed—a member of the PDCD10-GCKIII kinase module we name PGCKA1. Genome-wide pooled overexpression screens using a barcoded library of human open reading frames identify chromosomal regions, including chr4p, that suppress proliferation when overexpressed in a context-dependent manner, implicating network interactions. Together, these results shed light on the early emergence of complex aneuploid karyotypes involving chr4p and adaptive landscapes shaping breast cancer genomes. [Display omitted] •Chr4p loss evolves early in TNBC•Chr4p loss enhances growth•C4orf19 (PGCKA1) tumor suppressor Kuzmin et al. report that chromosome 4p loss evolves early in triple-negative breast cancer (TNBC) and is associated with enhanced proliferation. C4orf19 (PGCKA1) is a tumor suppressor. Certain regions, including chr4p, suppress proliferation when overexpressed, differentially implicating network rewiring. This study illuminates the early emergence of complex aneuploid karyotypes in TNBC.